Normocaloric Diet Restores Weight Gain and Insulin Sensitivity in Obese Mice - Lombardo, Giovanni Enrico; Arcidiacono, Biagio; De Rose, Roberta Francesca; Lepore, Saverio Massimo; Costa, Nicola; Montalcini, Tiziana; Brunetti, Antonio; Russo, Diego; De Sarro, Giovambattista; Celano, Marilena (Frontiers in Endocrinology, 2016)
An increased incidence of obesity is registered worldwide, and its association with insulin resistance and type 2 diabetes is closely related with increased morbidity and mortality for cardiovascular diseases. A major clinical problem in the management of obesity is the non-adherence or low adherence of patients to a hypo-caloric dietetic restriction. In this study we evaluated in obese mice the effects on insulin sensitivity of shifting from high-calorie foods to normal diet. Male C57BL/6JolaHsd mice (n=20) were fed with high fat diet for a 24 weeks period. Afterwards, body weight, energy and food intake were measured in all animals, together with parameters of insulin sensitivity by homeostatic model assessment of insulin resistance and plasma glucose levels in response to insulin administration. Moreover, in half of these mice, Glut4 mRNA levels were measured in muscle at the end of the high fat treatment, whereas the rest of the animals (n=10) were shifted to normocaloric diet for 10 weeks, after which the same analyses were carried out. A significant reduction of body weight was found after the transition from high to normal fat diet, and this decrease correlated well with an improvement in insulin sensitivity. In fact, we found a reduction in serum insulin levels and the recovery of insulin responsiveness in terms of glucose disposal measured by insulin tolerance test and Glut4 mRNA and protein expression. These results indicate that obesity related insulin resistance may be rescued by shifting from high fat diet to normocaloric diet.